The Impact of Public Participation Towards Waste Management In Tataaran Patar Village of South Tondano District - Mantiri, Jeane (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2018)
Garbage is a main issues discussed by many people, as we all know the amount of litter in Indonesia each year has increased, production of urban waste in Indonesia amounted to 38.5 million tons/ year or when averaged per-day amounted 200,000 tonnes/ day. If viewed in terms of waste management, it is known that 68% of the waste is transported and dumped, buried 9%, 6% is processed into compost and recycled, 5% was burned, and 7% of the waste is not managed. Trash if not handled properly will cause the unpleasant smell, the source of various diseases, blockage of waterways and can also cause flood. It was found by researcher in direct observation in the Village of Tataaran Patar, District of South Tondano. One of the main factors is the lack of public awareness on environment especially trash management boils down to the lowest participation rate.